Inter-laminar micro-endoscopic discectomy versus microdiscectomy in single-level posterolateral lumbar disc herniation: A comparative study - Mohamed Mohi Eldin; Ahmed Salah El Din Hassan; Omar Youssef Abdallah AboHamed; Ahmed Abdelaziz Nazem Hassan; Ahmed Hussein Omar (Journal of Craniovertebral Junction and Spine)
Background: Patients with neurological impairments or those unresponsive to conservative therapy may undergo surgical discectomy. The techniques include open discectomy (OD), microdiscectomy (MD), microendoscopic discectomy (MED), and percutaneous endoscopic discectomy. MED combines the benefits of MD and OD with minimal tissue damage. This study compared MD versus MED outcomes in patients with sciatica from lumbar disc herniation. Patients and Methods: This prospective clinical study included 50 patients who underwent single-level discectomy at Cairo University Hospital. The patients were divided into two groups: 25 patients who underwent MD in Group I and 25 who underwent MED in Group II. Results: In our study, 64% (16/25) of the MED group rated their postoperative condition as excellent, 28% (7/25) as good, 4% (1/25) as fair, and 4% (1/25) as poor, according to the modified McNab criteria. In the MD group, 60% (15 patients) reported excellent satisfaction; 28% (7 patients), good; 8% (2 patients), fair; and 4% (1 patient), poor satisfaction. Overall, 90% (45 patients) of patients across both groups had excellent to good outcomes, irrespective of the discectomy type. When categorizing excellent and good outcomes as successes and fair and poor as failures, the MED group’s success rate was 92%, compared to 88% for MD. There was no significant difference in patient satisfaction between the two groups. Conclusion: MED and MD showed equivalent efficacy in treating radicular pain caused by lumbar disc herniation. Patients in both groups showed significant improvements in Visual Analog Scale (VAS) and Oswestry Disability Index (ODI) scores. No significant differences were found between the groups in VAS, ODI, or complication rates, validating both surgical techniques for lumbar disc herniation. Compared with OD, MED showed reduced blood loss, smaller incisions, shorter hospital stays, and longer operation times. Although MED requires a steep learning curve, it remains safe even during the initial learning period, with outcomes and complication rates similar to those of MD.